Manchas de ejaculado pré e pós-vasectomia: pureza e quantidade de DNA recuperado após 10 anos de armazenamento - Mautoni, Carolina [UNIFESP] (2017)
The absence of sperm in the material collected from rape victims may be due to several factors, including the fact that the offender may have azoospermia, condition, for example, as a result of a successful vasectomy. There are also situations in which the only material available for analysis is derived from traces like semen stains on the victim's clothing. The objectives of this study were to assess the possibility of obtaining autosomal STR profile and STR-Y in seminal fluid stains, stored for 10 years and establish appropriate methodology for cases of traces from sexual aggression, pending for analysis and inclusion in databases (BNPG). Materials and Methods: Biological samples of seminal fluid pre and post-vasectomy, derived from 33 vasectomized individuals, preserved in cotton fabric since 2004, and the same was stored properly, in cardboard boxes, were used. In this study, the DNA material was extracted by QIAmp micro kit (Qiagen) and quantified by Real Time PCR technique, using the Quantifiler Duo DNA Quantification Kit following the manufacturer's instructions. Amplification was done through PowerPlex® ESI 17 Pro System, PowerPlex® FUSION and PowerPlex® 23-Y systems, and, analyzed on the ABI 3500 sequencer using the Gene MapperTM IDX version 1.2 program. We conclude that it is possible to obtain autosomal STR and STR-Y profile from extracted stains of semen preserved in cotton fabric for long periods. The colorless of cotton was an advantage for the study and facilitated the extraction in order not to offer PCR inhibitors. Still on this question, it is necessary to emphasize that even large elapsed time between the completion of the samples and the current study (10 years), these were particularly suitable degree of purity, and all profiles were obtained. The commercial DNA extraction kits present reproducibility and applicability of this type of material. Although in infima amount of biological materials (stain containing 30 uL of seminal liquid from vasectomized individuals in fabric), the methodology used in DNA extraction is reproducible and applicable to the stored cases. Considering the difficulty of obtaining genetic profile cases of sexual crime, analysis of fabric stains should be prioritized in the universe of the accumulated samples and stored for long periods.